From Public Assets to Corporate Capital: Rethinking the Legal Status of Regional Assets Used as Capital and Collateral in Regional State-Owned Enterprises (BUMD) - Ahmad Zuhairi; M Riadhussyah; Alwafi Ridho Subarkah; Eman Suparman; Muhamad Amirulloh (Faculty of Law, Universitas Sebelas Maret, 2026)
The legal position of regional assets utilised as capital participation in Regional State-Owned Enterprises (BUMD) engenders legal ambiguity, especially concerning their categorisation as state finances and their application as collateral in collaboration with third parties. This problem is crucial because different interpretations could make BUMD management criminally responsible if company losses are seen as state losses. This study investigates the status of regional assets designated for capital involvement within state finances and their potential use as collateral. The study utilises a normative legal methodology encompassing legislative, conceptual, and analytical frameworks. The findings indicate that regional assets conveyed as capital participation represent a legitimate transfer to the business as an independent legal entity and ought not to be regarded as state losses. However, assets that are classified as usage rights are still regional property and cannot be used as collateral. This study suggests that the laws of state finance, corporate law, and anti-corruption law should all be made to work together. It also states that clearer legal regulations should be established on the management of regional assets in BUMD to ensure the law is unambiguous.